Interrelationship of BMI and steroids on glycaemic levels in patient on chemotherapy - Mohammed, Riyaz; Jaiswal, Rajiv Kumar; Manuel, Rinu (International Journal of Research in Medical Sciences, 2016)
Background: This study was conducted to determine the interaction and interrelationship of BMI and steroids on blood glucose levels. Methods: To ascertain the interaction we had selected 383 cancer patients on chemotherapy. Inclusion criteria were Age : 12years - 70 years, FBS Between 100-126mg/dl, PLBS up to 140mg/dl, other routine parameters are checked like, Serum Creatinine, Microalbuminuria, HbA1c, Lipids Profile (Total cholesterol, Triglycerides, LDL, VLDL, HDL), Retinal examination, Chest X-ray , ECG. Patients having Hypertension, Coronary artery disease, CVD or acute and chronic complication of diabetes were excluded from the study. Results: During the study we have seen that patients who were pre-diabetics along with higher BMI were prone to develop diabetes which could have been precipitated due to steroids. Patients with BMI of 25 and 30 should be viewed as medically significant and worthy of therapeutic intervention, especially in the presence of risk factors that are influenced by adiposity, such as hypertension, hyperglycemia, insulin resistance, dyslipemia, cancer. Conclusions: The present study was done to highlight strict glycaemic control, (FBS <110 &PLBS <140-160 mg/dL). Patient on steroids during the chemotherapy with all these predisposing factors are vulnerable to develop Diabetes. This study is very significant as it outlines the necessity of awareness and precautions to be observed when dealing with patients with raised BMI without diabetes mellitus who are also likely to go in to hyperglycaemic and in extreme cases even ketoacidosis. Patients with high BMI and Prediabetes are prone to develop diabetes. Patient on these chemotherapy drugs like L- Asparginase, Streptozocin and Cytokine interferon – alpha are associated with drug induced insulin dependent diabetes mellitus.